Plasma metabolites of Kampung chicken (Gallus gallus domesticus) in peatland free-range system with differences of vegetation. Issue 1 (June 2021) - Fitra, D; Ulupi, N; Arief, I I; Mutia, R; Abdullah, L; Erwan, E
Abstract: Vegetation in free range rearing systems can be obtained from grass or legumes. The aims of this study was to investigate the effect of different vegetation on free range systems in peatlands on plasma metabolites of kampung chickens, including concentration of cholesterol (CHO), triglycerides (TG), and glucose (GLU). This experimental study used two hundred and ten kampung chickens with a completely randomized design of 4 treatments with 5 replications. Each paddock was placed in a portable housing. Twelve kampung chickens aged 5-12 weeks were reared in different types of vegetation with a density of 6.67 m 2 /head. The treatment without vegetation was reared in the postal housing. At the end of the study, blood was collected from the jungularis vein to observe plasma metabolites. The results showed that the maintenance system and differences in vegetation types had a significant effect (P<0.05) on CHO, TG and GLU. The highest TG was in the Axonopus compressus treatment, GLU was in the Indigofera zollingeriana treatment. while the lowest CHO was in the control or without vegetation. The conclusion of this study was the paddock planted with Indigofera zollingeriana can reduce CHO levels of kampung chickens in addition to control treatment.